HIBRID ALAMI ANTARA ARENGA PINNATA DAN A. OBTUSKOLIA DI KEBUN RAYA BOGOR - NANDA UTAMI (BERITA BIOLOGI, 1986)
NANDA UTAMI. 1986, Natural hybrid between A. pinnata and A. Obtusifolia in Bogor Botanical Garden.Berita Biologi 3(6): 297 - 300.The morphology and leaf anatomy of three collections of Arenga of incertain identity and grown in Bogor Botanical Garden are investigated and i compared with other species. The investigation showed that the characters of these collections oscillate between A pinnata and A. obtusifolia. Consequen tly it is suggested that the plants probably represent a natural hybrid of these two species.